WorkChoices and family-friendly working hours: An assessment of data sources - Jefferson, Therese; Preston, Alison (Centre for Workplace Culture Change RMIT, 2007)
When the Australian Federal Government introduced the WorkChoices legislation in 2006, one of its stated aims was to facilitate the negotiation of 'family-friendly' employment arrangements. This article assesses our capacity to achieve an accurate picture of 'family-friendly' arrangements in the new regulatory regime and examines the adequacy of publicly available indicators of women's employment status. We focus specifically on the capacity of current data to monitor 'family-friendly' employment arrangements in the form of flexible working hours and find that while there are a range of potential indicators, few will give a complete assessment of how women are faring. We conclude that there is ample capacity to reduce the fragmentation of currently available information and to increase the regularity with which it is collected. There is also a need for additional research to determine the indicators that might be most relevant to women in vulnerable positions in the workforce.